Synthesis of a one-dimensional atomic crystal of vanadium selenide (V2Se9) - Oh, Seungbae; Chae, Sudong; Kim, Bum Jun; Choi, Kyung Hwan; Jang, Woo Sung; Jang, Jimin; Hussain, Yasmin; Lee, Dong Kyu; Kim, Young Min; Yu, Hak Ki; Choi, Jae Young (RSC Advances, 2018)
The synthesis and nanoscale dispersion of a new one-dimensional (1D) material, V2Se9, in which chain-shaped molecular units with strong covalent bonds are assembled in a crystal structure via weak van der Waals attraction between chains, were successfully carried out. V2Se9 is synthesized by solid-state reaction and additional heat treatment. The synthesized V2Se9 has excellent thermal stability up to 400 °C and has been experimentally confirmed to be dispersed up to ∼20 nm or less through a specific solvent dispersion. The covalently bonded V2Se9 chain, when isolated from its bulk material, is expected to exhibit unique quantum physical properties owing to the confinement of electrons in the 1D chain structure and the absence of inter-chain interactions, as demonstrated in the case of graphene and other 2D materials. Therefore, the novel 1D material of V2Se9, as an extension of the current 2D material, is expected to create a new class of materials that will be of significant interest to the materials science and nanotechnology communities for new device applications.
Keywords: Atomic crystals; Bulk materials; Covalently bonded; Interchain interactions; Molecular units; Nanoscale-dispersion; Solvent dispersions; Van der Waals attraction